2016
DOI: 10.5301/jbm.5000186
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of ERCC2 Gene in Head and Neck Cancer is Associated with Aggressive Tumors: A Systematic Review and Case-Control Study

Abstract: Our data suggest that deregulation of ERCC2 in HNC has the potential to predict a more aggressive cancer phenotype and may be considered a possible biomarker for improved diagnosis and prognosis of HNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Genetic alterations of this gene have been linked to increased chemotherapy-sensitivity, especially to cisplatin [ 28 , 29 , 30 ]. Interestingly, ERCC2 has also been implicated in a recent meta-analysis in higher tumor stage and grade, and a positive correlation with Ki-67 in HNSCC, suggesting a more aggressive tumor phenotype [ 31 ]. However, the hazard ratio (HR) of ERCC2 ranged between 0.42 and 2.07 in the three respective publications ( Table S1 ) in our dataset, making a definitive interpretation difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic alterations of this gene have been linked to increased chemotherapy-sensitivity, especially to cisplatin [ 28 , 29 , 30 ]. Interestingly, ERCC2 has also been implicated in a recent meta-analysis in higher tumor stage and grade, and a positive correlation with Ki-67 in HNSCC, suggesting a more aggressive tumor phenotype [ 31 ]. However, the hazard ratio (HR) of ERCC2 ranged between 0.42 and 2.07 in the three respective publications ( Table S1 ) in our dataset, making a definitive interpretation difficult.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the expression of ERCC2 was associated with the expression of Ki-67 and an aggressive cancer phenotype and concluded that ERCC2 might be used as a biomarker for improved diagnostic and prognostic value in head and neck cancer. [ 36 ]. Huang et al analyzed ERCC2 expression by immunohistochemistry in 180 colorectal cancer patients with adjuvant chemotherapy and showed that ERCC2 was not related to survival time; moreover, similar results were observed in a study by Kassem et al [ 8 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, REG1 was shown to be significantly associated with survival in head and neck cancer [4]. The PD-L1 expression value was validated to have impact on many processes [5], and ERCC2 was reported to be associated with aggressive HNSCC [6]. Expression of C1GALT1 predicts the poor survival of head and neck cancer [7].…”
Section: Introductionmentioning
confidence: 99%